2021
DOI: 10.1016/j.meatsci.2020.108317
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumers' perceptions towards Iberian pig production and animal welfare

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 65 publications
1
44
0
1
Order By: Relevance
“…Also, specific production system (e.g. jamon iberico) are subject to regulations perceived to be consistent with higher animal welfare standards ( García-gudiño et al, 2021 ). Therefore - until more direct indicators and data bases are developed - we suggest using the share of organic and animal welfare certified animal products.…”
Section: The Food System Sustainability Compassmentioning
confidence: 99%
“…Also, specific production system (e.g. jamon iberico) are subject to regulations perceived to be consistent with higher animal welfare standards ( García-gudiño et al, 2021 ). Therefore - until more direct indicators and data bases are developed - we suggest using the share of organic and animal welfare certified animal products.…”
Section: The Food System Sustainability Compassmentioning
confidence: 99%
“…Zander and Hamm [48] discuss the relevance of ethical attributes for the marketing of organic foods, including not only environmental aspects of organic food, but also aspects linked with animal welfare. Many research works reported that animal welfare influences people's food decisions [49], particularly when consuming eggs [50], milk [51] or meat [52,53].…”
Section: Food Choices Related With Environmental and Sustainability Issuesmentioning
confidence: 99%
“…The low price was the average price for pork from white pigs while the high price was the average price for pork from Iberian pigs. Farm attributes evaluated in this study were chosen because of their importance on Iberian pig production and pork consumption as reported in other studies [28,29].…”
Section: Conjoint Analysismentioning
confidence: 99%